Differentiation of Vascular Stem Cells Contributes to Ectopic Calcification of Atherosclerotic Plaque. (27th February 2016) - Leszczynska, Aleksandra; O'Doherty, Aideen; Farrell, Eric; Pindjakova, Jana; O'Brien, Fergal J.; O'Brien, Timothy; Barry, Frank; Murphy, Mary
Abstract: The cellular and molecular basis of vascular calcification (VC) in atherosclerosis is not fully understood. Here, we investigate role of resident/circulating progenitor cells in VC and contribution of inflammatory plaque environment to this process. Vessel-derived stem/progenitor cells (VSCs) and mesenchymal stem cells (MSCs) isolated from atherosclerotic ApoE −/− mice showed significantly more in vitro osteogenesis and chondrogenesis than cells generated from control C57BL/6 mice. To assess their ability to form bone in vivo, cells were primed chondrogenically or cultured in control medium on collagen glycosaminoglycan scaffolds in vitro prior to subcutaneous implantation in ApoE −/− and C57BL/6 mice using a crossover study design. Atherosclerotic ApoE −/− MSCs and VSCs formed bone when implanted in C57BL/6 mice. In ApoE −/− mice, these cells generated more mature bone than C57BL/6 cells. The atherosclerotic in vivo environment alone promoted bone formation by implanted C57BL/6 cells. Un-primed C57BL/6 VSCs were unable to form bone in either mouse strain. Treatment of ApoE −/− VSC chondrogenic cultures with interleukin (IL)-6 resulted in significantly increased glycosaminoglycan deposition and expression of characteristic chondrogenic genes at 21 days. In conclusion, resident vascular cells from atherosclerotic environment respond to the inflammatory milieu and undergo calcification. IL-6 may have a role in aberrant differentiation of VSCs contributing to vascular calcification in atherosclerosis.